Incorporating longitudinal pediatric patient-centered outcome measurement into the clinical workflow using a commercial electronic health record: a step toward increasing value for the patient. (15th September 2015) - Carberry, Kathleen; Landman, Zachary; Xie, Michelle; Feeley, Thomas; Henderson, John; Fraser, Charles
Abstract: Patient-centered outcomes measurement provides healthcare organizations with crucial information for increasing value for patients; however, organizations have struggled to obtain outcomes data from electronic health record (EHR) systems. This study describes how Texas Children's Hospital customized a commercial EHR system and assembled a cross-functional team to capture outcomes data using existing functionality. Prior to its installation and customization, no surgical subspecialties besides the congenital heart and transplant surgery groups conducted prospective, patient outcomes measurement, but by 2015, the outcomes of over 1300 unique patients with supracondylar fractures, cleft lip and/or palate, or voiding dysfunction had been tracked. Key factors for integrating outcomes measurement into the clinical workflow include ongoing communication between cross-functional teams composed of clinicians and technical professionals, an iterative design process, organizational commitment, and prioritizing measurement as early as possible during EHR optimization.